A measurement of the ratio of the W and Z cross sections with exactly one associated jet in pp collisions at √s=7 TeV with ATLAS - Aad, Georges; Anders, Gabriel; Andrei, George Victor; Childers, J. Taylor; Davygora, Yuriy; Dietzsch, Thorsten; Geweniger, Christoph; Hanke, Paul; Henke, Michael; Khomich, Andrei; Kluge, Eike-Erik; Kugel, Andreas; et al. (Physics letters, 2012)
The ratio of production cross sections of the W and Z bosons with exactly one associated jet is presented as a function of jet transverse momentum threshold. The measurement has been designed to maximise cancellation of experimental and theoretical uncertainties, and is reported both within a particle-level kinematic range corresponding to the detector acceptance and as a total cross-section ratio. Results are obtained with the ATLAS detector at the LHC in pp collisions at a centre-of-mass energy of 7 TeV using an integrated luminosity of 33 pb−1. The results are compared with perturbative leading-order, leading-log, and next-to-leading-order QCD predictions, and are found to agree within experimental and theoretical uncertainties. The ratio is measured for events with a single jet with pT>30 GeV to be 8.73±0.30(stat)±0.40(syst) in the electron channel, and 8.49±0.23(stat)±0.33(syst) in the muon channel.